Chromosome Pairing in Hybrid Progeny between Triticum aestivum and Elytrigia elongata - He, Fang; Xing, Piyi; Bao, Yinguang; Ren, Mingjian; Liu, Shubing; Wang, Yuhai; Li, Xingfeng; Wang, Honggang (Frontiers in Plant Science, 2017)
In this study, intergeneric hybrids F1, F2, BC1F1, BC1F2 and BC2F1 from Elytrigia elongata and Triticum aestivum crosses were produced to study their chromosome pairing behaviour. The average E. elongata chromosome configuration of the two F1 hybrids agreed with the theoretical chromosome configuration of 21I+7II, indicating that the genomic constitution of this F1 hybrid was ABDStStEeEbEx. Compared with the BC1F1 generation, the BC2F1 generation showed a rapid decrease in the number of E. elongata chromosomes and the BC1F2 generation showed a more extensive distribution of E. elongata chromosomes. In addition, pairing between wheat and E. elongata chromosomes was detected in each of the wheat-E. elongata hybrid progenies, albeit rarely. Our results demonstrated that genomic in situ hybridization (GISH) using an E. elongata genomic DNA probe offers a reliable approach for characterizing chromosome pairing in wheat and E. elongata hybrid progenies.